2014
DOI: 10.1016/j.eururo.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase 9 Expression Increases with Vascular Endothelial Growth Factor–Targeted Therapy and Is Predictive of Outcome in Metastatic Clear Cell Renal Cancer

Abstract: BackgroundThere is a lack of biomarkers to predict outcome with targeted therapy in metastatic clear cell renal cancer (mccRCC). This may be because dynamic molecular changes occur with therapy.ObjectiveTo explore if dynamic, targeted-therapy-driven molecular changes correlate with mccRCC outcome.Design, setting, and participantsMultiple frozen samples from primary tumours were taken from sunitinib-naïve (n = 22) and sunitinib-treated mccRCC patients (n = 23) for protein analysis. A cohort (n = 86) of paired, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…The final finding was that despite ITH, consistent chromosomal, RNA and protein changes to the targets of sunitinib were seen with treatment, in keeping with our previous findings regarding consistent changes in CAIX protein expression following sunitinib treatment (12). Notable CNVs identified were losses of the renal cancer driver genes SETD2, BAP1, VHL, and PBRM1 (latter two genes also had a significantly lower level of gene expression) following sunitinib therapy (20).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The final finding was that despite ITH, consistent chromosomal, RNA and protein changes to the targets of sunitinib were seen with treatment, in keeping with our previous findings regarding consistent changes in CAIX protein expression following sunitinib treatment (12). Notable CNVs identified were losses of the renal cancer driver genes SETD2, BAP1, VHL, and PBRM1 (latter two genes also had a significantly lower level of gene expression) following sunitinib therapy (20).…”
Section: Discussionsupporting
confidence: 70%
“…Reverse phase protein array (RPPA) samples protein levels were determined and slides spotted as described previously (7,12). Briefly, batch effects across the three slides per marker were mitigated using ComBat (13) and normalized (VSN; 14).…”
Section: Reverse Phase Protein Arraysmentioning
confidence: 99%
“…Of importance, a treatment-induced increase of CA9 in our patients was associated with improved PFS and OS. Although this may seem counterintuitive, increased intratumoral CA9 expression in patients with advanced renal cell carcinoma treated with sunitinib for 18 weeks has also been associated with better OS (43). An increased level in CA9 has also been observed in glioblastoma patients during treatment with cediranib and chemoradiation or chemoradiation alone (31).…”
Section: Discussionmentioning
confidence: 80%
“…Older data from our institution suggested that CAIX had a role as a predictor of treatment response to high-dose interleukin 2 (IL-2) therapy. This finding was externally validated and prospectively confirmed by our own institution [2,3]; however, a large, multicenter, prospective, randomized trial (SELEC trial) conducted by the Cytokine Working Group failed to confirm a predictive role of CAIX for treatment response to IL-2. More recently, retrospective studies had suggested that there may be a predictive role for CAIX expression in patients treated with targeted therapy with sorafenib [4]; however, this finding could not be confirmed in a larger cohort of the TARGET (Treatment Approaches in Renal Cancer Global Evaluation Trial) study.…”
mentioning
confidence: 62%
“…We read with great interest the current study of Stewart et al, who described the independent association of carbonic anhydrase IX (CAIX) expression and survival outcomes in patients with clear cell renal cell carcinoma (ccRCC) treated with sunitinib [1]. Despite having been approved for >7 yr, effective predictive biomarkers for sunitinib treatment response are still lacking.…”
mentioning
confidence: 89%